Sobrecarga em mulheres que cuidam de crianças e adolescentes com transtornos mentais - Moraes, Marina Nascimento de (2020)
Objective: To analyze the burden experienced by women caregivers of children and adolescents with mental disorders, identifying the factors linked to burden and the coping strategies that are used by those who have high subjective burden. Method: Study carried out in two stages, in an outpatient clinic for childhood and adolescence psychiatry in a capital city in Northeastern Brazil. The first step was a cross-sectional, correlational study, with a quantitative approach, developed with 164 caregivers, using a socioeconomic questionnaire and the Scale of Burden of Family Members of Psychiatric Patients. The data from this stage were tabulated and analyzed using statistical software, using descriptive statistics and inferential analysis. In the second stage, a qualitative, descriptive, exploratory study, individual, semi-structured interviews were conducted with 14 caregivers. The interviews were transcribed and analyzed with the aid of software. Results: In the first stage, an average total caregiver burden of 3.07 was observed, while the averages of objective and subjective burdens were 3.23 and 2.45, respectively. We identified high objective burden related to assistance in activities of daily living and high subjective burden resulting from living with problematic behaviors. There was also a significant correlation between the number of people the caregiver provides care for, the age of the caregiver and the individual cared for with both objective and subjective burden. The data from the second stage point to the formation of three main factors linked to burden among caregivers with high subjective burden: the lack of support in caring, the various responsibilities that these women have and the lack of knowledge about the best management and pathology that affects minors. As for coping strategies, spirituality, the practice of pleasurable activities and the search for social support were the most present. Conclusion: The data from this research show that burden is present at high levels in the daily lives of these collaborators, being related to different factors and coping strategies. The recognition of factors linked to caregiver burden allows to identify more clearly the needs of these caregivers, thus enabling services and the State to be responsible for this care, through public policies and the implementation of actions aimed at the well-being and aspirations of these women.